Association between sleep characteristics and mild cognitive impairment in elderly people - An, C.; Yu, L.; Wang, L.; Jin, G.; Song, M.; Zhu, Q.; Jia, H.; Liu, K.; Wang, M.; Wang, X. (Нейрофизиология, 2014)
We compared the sleep quality indices between patients with mild cognitive impairment (MCI) and normal elderly subjects and analyzed the effects of sleep characteristics on cognitive functions. Cases of MCI patients (320 persons, MCI group) and 630 normal elderly with matched age, gender, and level of education (control group) were enrolled in this study. The Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep characteristics. The Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) were used to assess cognitive function. There were 110 (34.3%) and 170 (27%) cases with sleep disorders in the MCI and control groups, respectively (P < 0.01). There was a significant difference of total PQSI scores between the two groups, and the scores of sleep duration (factor III) and habitual sleep efficiency (factor IV) in the MCI group were significantly lower than those in the control group. Total PQSI scores negatively correlated with MoCA scores and MMSE scores. MoCA scores negatively correlated with scores of the sleep latency (factor II), sleep duration (factor III), and habitual sleep efficiency (factor IV), while MMSE scores negatively correlated with scores of factor III and factor IV. The scores of attention and calculation, reading and language understanding, and visuospatial function (MMSE), and also of visuospatial/executive function, attention, and clock-drawing test (MoCA) in MCI patients without sleep disorders were significantly higher than those in MCI patients with such disorders. The incidence of sleep disorders is higher in patients with MCI, compared with normal elderly. Effects of sleep disorders on cognitive functions are mainly reflected in the state of attention, and visuospatial/executive function.